Pengelolaan Sampah Kreatif: Solusi Praktis Mengubah Limbah Menjadi Barang Bernilai Guna di SMP Negeri 23 Bandar Lampung - Fikri Aziz; Beti Susilawati; Rini Kurnia Sari; Eva Anggraini (INDO PUBLISHING, 2026)
Waste management has become a crucial issue in school environments as it affects cleanliness, health, and students’ ecological awareness. SMP Negeri 23 Bandar Lampung faces the challenge of low student concern in sorting and utilizing waste, which requires innovative approaches through creative waste management. This study aims to provide a practical solution by transforming waste into useful products while enhancing students’ skills and environmental awareness. The method applied was a participatory approach involving creative recycling workshops, direct observation, and mentoring activities where students produced simple products such as handicrafts, plant pots, and household tools from waste materials. The results indicate that creative waste management not only reduces waste volume but also fosters creativity, collaboration, and responsibility among students toward their school environment. Therefore, creative-based waste management can serve as a practical solution as well as a sustainable educational medium in schools.